2020
DOI: 10.12688/wellcomeopenres.16293.2
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on public health interventions in the management of the COVID-19 pandemic in Thailand

Abstract: Background: Any government needs to react quickly to a pandemic and make decisions on healthcare interventions locally and internationally with little information regarding the perceptions of people and the reactions they may receive during the implementation of restrictions. Methods: We report an anonymous online survey in Thailand conducted in May 2020 to assess public perceptions of three interventions in the Thai context: isolation, quarantine and social distancing. A total of 1,020 participants, of whom 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
(8 reference statements)
2
5
0
Order By: Relevance
“…By contrast, participants who lived in provincial areas and had less contact with other people outside their home reported less compliance with the public health measures. These findings are consistent with the results of the quantitate part of the Thai SEBCOV study [31].…”
Section: Viewssupporting
confidence: 91%
See 3 more Smart Citations
“…By contrast, participants who lived in provincial areas and had less contact with other people outside their home reported less compliance with the public health measures. These findings are consistent with the results of the quantitate part of the Thai SEBCOV study [31].…”
Section: Viewssupporting
confidence: 91%
“…Participants in this study generally expressed agreement with government-imposed public health measures. This confirms and explains the findings from our quantitative SEBCOV study [30,31], and other studies that have reported widespread agreement with governmentimposed COVID-19 NPIs and high levels of compliance with public health measures among Thai residents, including voluntary behaviour changes before official government regulations were implemented [30,31,51]. By offering an in-depth exploration of the views of public health measures, this study helps to shed light on the reasons and motivations for high selfreported compliance and agreement among a small number of Thai residents.…”
Section: Viewssupporting
confidence: 90%
See 2 more Smart Citations
“…We have also conducted a preliminary analysis of unweighted Thai survey responses during May 2020, which includes more detailed breakdowns by regions within Thailand. 66 …”
Section: Discussionmentioning
confidence: 99%